Menanamkan Budaya Ilmiah di Kalangan Pelajar Melalui Model SBR (School By Research) di SMAN 1 Pare-Kediri - Azizah, Nurul; Dyah widowati (ABIDUMASY, 2026)
Indonesia’s economic growth has stagnated at around 5%, causing the nation to lag in innovation compared to Vietnam and Malaysia. One key factor is the weak research culture, which results in less impactful innovations. To overcome this, the East Java provincial government launched the School by Research program for senior high schools. SMAN 1 Pare, already implementing a research-oriented approach through the Independent Learning Curriculum, became a strategic starting point. The program aims to build a research culture among students through continuous socialization, orientation, and training in research practices. Conducted as a community service initiative, it combines educational outreach with pre-test and post-test assessments to measure improvements in students’ understanding of scientific writing. Results showed a notable increase in their academic writing skills. Peer learning was also emphasized, with experienced students guiding peers to foster collaborative growth. A scientific writing module, specifically tailored for high school students, was developed and formally handed over to the school as a sustainable resource. This initiative is expected to become a foundation for further activities, such as scientific writing competitions, to enhance creativity, critical thinking, and innovative expression. By sustaining the School by Research model, Indonesia can gradually strengthen its research culture, contributing to improved national innovation performance.